HUBUNGAN TINGKAT PENGETAHUAN, SIKAP DAN TINGKAT DUKUNGAN KELUARGA DENGAN PRAKTIK PERAWATAN DIRI PADA PENDERITA KUSTA DI KOTA SEMARANG - Hidayah, Elma Nur; Ginandjar, Praba; Martini, Martini; Udiyono, Ari (Fakultas Kesehatan Masyarakat, 2020)
Disability due to leprosy can be prevented by self-care practices. The implementation of self-care practices in people affected by leprosy in the Semarang City has not been implemented optimally. The proportion of level II disabilities of people affected by leprosy in Semarang from 2017 to 2018 increased from 21% to 26%, so that the national target for disability in leprosy has not yet reached the target of 5%. Based on the results of a preliminary study of self-care practices, there are 50% of people affected by leprosy who are not good at self-care.The purpose of this study was to analyze the factors related to the practice of self-care in people with leprosy in Semarang City. The design of this study was cross sectional. The subjects of this study were leprosy sufferers in Semarang city in 2016-2018 who were still doing self-care were 52 leprosy patients.The sampling method used is total sampling. The statistical test used was the Chi-Square test with a confidence level of 95%. Statistical analysis showed that there was a relationship between the level of knowledge (p = 0.006 < 0,05) and the level of family participation (p = 0.012 < 0.05) with the practice of self-care practices in leprosy patients, while the attitude towards self-care (p = 0.052 >0.05) proved to be no relationship. It can be concluded that there is a relationship between attitude towards self-care and the level of regular self-care for people with leprosy in the city of Semarang. However, there is no relationship between the level of family support and self-care practices for people with leprosy.